The relationship between technique and score in tennis doubles -a study of male and female collegiate tennis players - Okamura, S.; Numata, K.; Kashiwagi, R. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
The purpose of this study was to clarify the relationship between the techniques used, number of rallies in doubles and the score of male and female collegiate tennis players. The last shot used at each point in thirty-one male and female doubles matches was classified into six categories, and the number of rallies was classified into four categories. Then, referring to Takahashi et al. (2006) and Roure (2014), we defined 30-30 as the important score, and compared the percentages of the techniques and the number of rallies used before and after that score, respectively. The results showed that male players tended to use significantly more ground strokes and less poach after the important score. On the other hand, although there was no significant difference in the techniques used by the female players, a comparison of the number of rallies before and after the important score revealed that the percentage of within four rallies was significantly lower and the percentage of over thirteen rallies was significantly higher for the female players after the important score. This suggests that male players chose groundstrokes to reduce the risk of making errors after the important score, while female players did not change the technique they used depending on the score, but tended to make fewer mistakes early on.